Analysis of Medicolegal Cases in a Tertiary Care Hospital of South Kerala (Indian Journal of Forensic Medicine & Toxicology, 2020)
Medicolegal cases (MLC) are presented to Emergency department (ED) of almost all hospitals in our nationafter the Supreme Court guidelines stating that ‘the paramount duty of a doctor is to save the life of aperson’. Hospitals should be equipped with infrastructure as well as treating doctors in combating such caseswhere documentation and treatment should be meticulously done.This study is conducted in a tertiary care hospital in South Kerala where profile of MLC was analysed duringthe years 2016 -17. A total of 10,001 cases were studied which is unique compared to previous studies.Males dominated in the MLC with road traffic accident (RTA), fall from height and work place injuriesformed the major share in the pattern of cases. Most of these cases were presented to ED between first andsixth hour of occurrence
Keywords: Medicolegal cases, Emergency department, demographic profile